Guided Photoluminescence from Integrated Carbon‐Nanotube‐Based Optical Waveguides. (9th September 2015) - Bodiou, Loïc; Gu, Qingyuan; Guézo, Maud; Delcourt, Enguerran; Batté, Thomas; Lemaitre, Jonathan; Lorrain, Nathalie; Guendouz, Mohammed; Folliot, Hervé; Charrier, Joël; Mistry, Kevin S.; Blackburn, Jeffrey L.; et al.
<x xml:space="preserve">Abstract</x> Thin films and ridge waveguides based on large‐diameter semiconducting single‐wall carbon nanotubes (s‐SWCNTs) dispersed in a polyfluorene derivative are fabricated and optically characterized. Ridge waveguides are designed with appropriate dimensions for single‐mode propagation at 1550 nm. Using multimode ridge waveguides, guided s‐SWCNT photoluminescence is demonstrated for the first time in the near‐infrared telecommunications window.